Hybrid Hydrogen Systems Stationary and Transportation Applications - Al-Hallaj, Said; Kiszynski, Kristofer (Green Energy and Technology,, 2011)
Renewable energy technologies have been used on a small scale for many years now. Issues of intermittency and cost have prevented their widespread use and acceptance. At present, discussion and research is aimed at moving the current global fossil fuels economy to one based on hydrogen as the universal energy carrier, with fuel cells as a means of converting this chemical energy to electrical energy. Hybrid Hydrogen Systems presents an original and comprehensive approach to hybrid energy system optimization, providing a much-needed systems approach to hydrogen energy applications. This book provides a comprehensive overview of the fundamentals of renewable power generation, conversion and storage, including: wind, solar photovoltaic power, biomass, batteries, fuel cells, and hydrogen. As well as proposing a unique approach to minimize the cost and maximize the reliability of hybrid energy systems, Hybrid Hydrogen Systems introduces the benefits of hydrogen as an energy carrier in the context of sustainability. This book will be of interest to researchers and practitioners working with hydrogen and fuel cells, as well as to policy makers and advocates of renewable energy. Hybrid Hydrogen Systems will also be a valuable tool for graduate and advanced undergraduate students studying renewable energy and the design and optimization of hydrogen energy systems, as well as for the lecturers who teach these subjects.